Spontaneous fulfillment of desire : harnessing the infinite power of coincidence - Chopra, Deepak (New York : Harmony Books, 2003)
Explains how to access the everyday coincidences of life and how to understand and reconnect with the underlying field of infinite possibilities in order to fulfill one's deepest desires and transform one's life
Matter, mind, and spirit -- Synchronicity in nature -- The nature of the soul -- Intention -- The role of coincidence -- Desires and archetypes -- Meditation and mantras -- The first principle : you are a ripple in the fabric of the cosmos -- The second principle : through the mirror of relationships I discover my non-local self -- The third principle : master your inner dialogue -- The fourth principle : intent weaves the tapestry of the universe -- The fifth principle : harness your emotional turbulence -- The sixth principle : celebrate the dance of the cosmos -- The seventh principle : accessing the conspiracy of improbabilities -- Living synchrodestiny.
88796
Keywords: Coincidence; Self-actualization (Psychology)